Temporal Stability of Lipid-Shelled Microbubbles During Acoustically-Mediated Blood-Brain Barrier Opening - Pouliopoulos, Antonios N.; Jimenez, Daniella A.; Frank, Alexander; Robertson, Alexander; Zhang, Lin; Kline-Schoder, Alina R.; Bhaskar, Vividha; Harpale, Mitra; Caso, Elizabeth; Papapanou, Nicholas; Anderson, Rachel; Li, Rachel; et al. (Frontiers in Physics, 2020)
Non-invasive blood-brain barrier (BBB) opening using focused ultrasound (FUS) is being tested as a means to locally deliver drugs into the brain. Such FUS therapies require injection of pre-formed microbubbles, currently used as contrast agents in ultrasound imaging. Although their behavior during exposure to imaging sequences has been well described, our understanding of microbubble stability within a therapeutic field is still not complete. Here, we study the temporal stability of lipid-shelled microbubbles during therapeutic FUS exposure in two timescales: the short time scale (i.e., μs of low-frequency ultrasound exposure) and the long time scale (i.e., days post-activation). We first simulated the microbubble response to low-frequency sonication, and found a strong correlation between viscosity and fragmentation pressure. Activated microbubbles had a concentration decay constant of 0.02 d-1 but maintained a quasi-stable size distribution for up to 3 weeks (< 10% variation). Microbubbles flowing through a 4-mm vessel within a tissue-mimicking phantom (5% gelatin) were exposed to therapeutic pulses (fc: 0.5MHz, peak-negative pressure: 300kPa, pulse length: 1ms, pulse repetition frequency: 1Hz, n=10). We recorded and analyzed their acoustic emissions, focusing on emitted energy and its temporal evolution, alongside the frequency content. Measurements were repeated with concentration-matched samples (107 microbubbles/ml) on day 0, 7, 14, and 21 after activation. Temporal stability decreased while inertial cavitation response increased with storage time both in vitro and in vivo, possibly due to changes in the shell lipid content. Using the same parameters and timepoints, we performed BBB opening in a mouse model (n=3). BBB opening volume measured through T1-weighted contrast-enhanced MRI was equal to 19.1±7.1 mm3, 21.8±14 mm3, 29.3±2.5 mm3, and 38±20.1 mm3 on day 0, 7, 14, and 21, respectively, showing no significant difference over time (p-value: 0.49). Contrast enhancement was 24.9±1.7 %, 23.7±11.7 %, 28.9±5.3 %, and 35±13.4 %, respectively (p-value: 0.63). In conclusion, the in-house made microbubbles studied here maintain their capacity to produce similar therapeutic effects over a period of 3 weeks after activation, as long as the natural concentration decay is accounted for. Future work should focus on stability of commercially available microbubbles and tailoring microbubble shell properties towards therapeutic applications.